Transgender Men and Lactation. Issue 1 (January 2015) - Wolfe-Roubatis, Emily; Spatz, Diane L.
<x xml:space="preserve">Abstract</x> Abstract Research examining needs of postpartum transgender men in relation to lactation and infant feeding is missing from nursing literature. Accordingly, little is known about how perinatal nurses can best support this unique subset of postpartum patients. Case studies presented here reveal that transgender men would appreciate care from nurses who are knowledgeable about transgender individuals and their healthcare needs, but this type of care is not always available. Nurses need more education about how to best support transgender patients and families in order to achieve optimal lactation and infant nutrition in this population.